Peningkatan Keaktifan dan Hasil Belajar IPA Siswa Kelas 5 SD Dengan Menggunakan Model Pembelajaran Problem Based Learning - Jihan Satila; Nur Azmi Alwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article aims to increase student activity and learning outcomes by implementing the problem based learning (PBL) learning model. In implementing the problem-based learning (PBL) model for fifth grade students, the main goal is for students to be able to understand science material and for students to become active in science learning. PBL is a learning model that uses everyday problems as a context for students to be directly involved in problem solving and gaining essential knowledge in science subjects.